UJI DAYA HAMBAT EKSTRAK DAUN CENGKEH (Syzygium aromaticum (L.) Merr. & L. M Perry.) TERHADAP PERTUMBUHAN BAKTERI Shigella dysenteriae - Iis Salihat; Orryani Lambui; Ramadanil Pitopang (Biology Department, Mathematics and natural science, Tadulako University, 2020)
Research about the inhibitory test of Syzygium aromaticum leaf extract on the growth of Shigella dysenteriae bacteria which aims to determine the effectiveness of S. aromaticum leaf extract in inhibited the growth of S. dysenteriae bacteria, knowing the concentration of leaf extract is effective in inhibited the growth of S. dysenteriae bacteria and the content of flavonoid compounds, saponins, tannins and alkaloids contained in leaves S. aromaticum, has been conducted from July until December 2016. Extraction method used is Maseration method. Inhibitory test extract on S. dysenteriae bacteria using disc diffusion method. This research was arranged in Completely Randomized Design with 6 treatments and 3 repetitions with extract concentration 30%, 45%, 60% and 75% and 2% Cotrimoxazole antibiotics as positive controls and Aquades as negative controls. The results showed that 75% extract concentration of S. aromaticum plant produced the largest drag zone compared to other concentrations of 17 mm. This indicates that S. aromaticum leaf extract has good inhibitory ability against S. dysenteriae bacteria.